2021
DOI: 10.21203/rs.3.rs-358513/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Caspofungin suppresses brain cell necroptosis in the ischemic stroke rat via up-regulation of Pellino3

Abstract: Purpose Pellino3, an ubiquitin E3 ligase, prevents the formation of the death-induced signaling complex in response to TNF-α via targeting receptor-interacting protein kinase 1 (RIPK1), and bioinformatics analysis predicts the interaction between Pellino3 and caspofungin, a common antifungal drug used in clinic. This study aims to explore the effect of caspofungin on brain injury in ischemic stroke and the underlying mechanisms. Methods The SD rat brains (or nerve cells) were subjected to 2h-ischemia (or 8h-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Spectroscopic analysis using 1 H-NMR,13 C-NMR, and DEPT (Table2) indicated that compound 2 comprises two methyl groups, five methines, five saturated non-protonated carbons, and one ketone carbonyl carbon(δC 175.94, δC 194.36). Its NMR profile is similar to brocaeloid C[23], with the distinction of an added succinimide substructure at N-15, where the ketone carbonyl carbon at C-16 is replaced by a hydroxyl carbon. The isoprene group is consistent with that in compound 1.…”
mentioning
confidence: 89%
“…Spectroscopic analysis using 1 H-NMR,13 C-NMR, and DEPT (Table2) indicated that compound 2 comprises two methyl groups, five methines, five saturated non-protonated carbons, and one ketone carbonyl carbon(δC 175.94, δC 194.36). Its NMR profile is similar to brocaeloid C[23], with the distinction of an added succinimide substructure at N-15, where the ketone carbonyl carbon at C-16 is replaced by a hydroxyl carbon. The isoprene group is consistent with that in compound 1.…”
mentioning
confidence: 89%